Reflecting on Pre-service Teachers ' Practicum in Tanzania: Avenue for Professional Inquiry, Discovery and Growth - Majani, William Pastory (Papers in Education and Development, 2022)
Abstract This paper is framed within Relational Cultural Theory (RCT) and Reflective in Practice Theory (RPT) lenses to explore the role of experiential learning in fostering professional inquiry growth, and relational building for six Canadian pre-service teachers posted to conduct practicum in Tanzania. This study uses field notes and reflective journal as main sources of data. The findings of this study indicated that practicum is an avenue to learn, unlearn and relearn about teaching. It is also a moment for novice teachers to connect and network with education stakeholders in other places or countries. Doing practicum in other cultures may stimulate collaborations such as global North and global South collaboration for a practicum done outside the country. However, acknowledging context as an integral part of experiential learning must be emphasized. In this case, interrogating assumptions and converging perspectives during practicum in a foreign country is a precursor towards effective teaching. Keywords: cross-culture, experiential learning, global north, global south, Tanzania